Urgency of Regulating Cryptocurrency Inheritance Features on Exchange Platforms to Ensure Legal Certainty for Heirs in Indonesia - Syaiful Malik; Taupiqqurrahman (Dinasti Research, 2026)
The development of cryptocurrency as a digital asset presents new challenges in inheritance law. Its decentralized nature and reliance on private keys pose a risk of rendering the asset permanently inaccessible if the owner passes away. This article, titled